An Analysis of the Social and Linguistic Construction of Artificial Intelligence - Pučko, David; Kolar, Staša (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
The purpose of this research is to highlight the important role that language and discourse play in the business world with regard to shaping society. We want to show that the way we use language to communicate can have a significant impact on societal development. We start from the premise that language is a central tool in the construction of social reality, and therefore the discourse used by companies plays a key role in shaping perceptions and values.  Given the rise of AI across various domains, our exploration focuses specifically on the economic discourse within the so-called “fourth revolution” –  the AI revolution. Throughout the paper, we hope to stimulate the interest of researchers from different disciplines to pay attention to the often overlooked category of language.